Māsu izglītojošais darbs medicīniskās apaugļošanas klīnikās Latvijā - Frolenoka, Beata (Latvijas Universitāte, 2017)
Maģistra darba tēmas izvēli „Māsu izglītojošais darbs medicīniskās apaugļošanas klīnikās Latvijā” noteikusi tās aktualitāte veselības un sociālā jomā. Latvijā no 2012. gada ļoti veiksmīgi darbojas Valsts apmaksāta neauglības ārstēšanas programma. Maģistra darba mērķis ir pēc intervijām un anketēšanas noskaidrot un analizēt māsu izglītojošo darbu medicīniskās apaugļošanas klīnikās. Lai sasniegtu izvirzīto mērķi, autore apkopoja un izanalizēja zinātnisko literatūru un citus avotus par medicīnas apaugļošanas pirmssākumiem un attīstību pasaulē un Latvijā. Liela uzmanība ir pieversta jautājumiem par neauglību un tās iemesliem, medicīnas apaugļošanas metodēm, ka arī medicīnas ētikas jautājumiem medicīniskās apaugļošanas procedūras laikā. Tiek apskatīts māsu darbs pacientu, donoru un grūtnieces izglītošanai. Ar pētniecības datu ievākšanas metodem - intervijām, novērošanas protokoliem un māsas anketām no trim neauglības ārstēšanas klīnikām Latvijā ir iegūta , līdz šim nepētīta, informācija par māsu izglītojošo darbu medicīnās apaugļošanas klīnikās, māsu personības pašizjūtu, par nepieciešamību un māsu vēlmēm papilddzināšanu iegūšanai. Pētījuma rezultātā tika apkopoti pieejamie dati un iegūta līdz šim nepublicēta informācija par māsu izglītojošo darbu medicīnās apaugļošanas klīnikās., māsu personības pašizjūtu, un papildzināšanu iegūšanas nepieciešamību . Darba mērķis tika sasniegts.

The choice of the theme of the master's thesis "Mass Educational Work in the Assisted Reproduction Clinics in Latvia" was preconditioned by its topicality in the health and social sectors. In Latvia, since the year 2012, the state-funded infertility treatment programme has been being implemented very successfully. The aim of the master's paper is to find out and analyse according to the interviews and questionnaires the nursing educational work in the assisted reproduction clinics. To achieve this goal, the author has summarised and analysed the scientific literature and other sources of medical fertilization inception and development in the world and in Latvia, on infertility and its reasons, on medical fertilization techniques, on medical ethical issues of assisted reproduction procedures; on nursing work, educating patients, donors and pregnant women, on the patient educational pedagogical methods. With the help of the research data collection on methods - interviews, observation protocols and questionnaires of the sisters, the before un-researched information from three infertility treatment clinics of Latvia has been obtained about nursing educational work in the medicine fertilization clinics on nurse personality self-feeling, and of the need and preferences of nurses to obtain additional knowledge. The paper consists of five chapters. In the first chapter, the author of the works considers the child conception possibilities, causes of fertility problems and their reasons, medical conception origins and development in the world and in Latvia, treatment possibilities and reproductive technology methods. In the second chapter of the work, the author considers the universal fundamental ethical principles and analyses the medical ethics aspects of nurse educational work in the assisted reproduction clinics of Latvia. In the third chapter of the work, the author analyses the application of nursing theory for the working purposes. In the fourth chapter of the work, the author considers the basic patient educational principles and methods. In the fifth chapter, the author presents the results of the researches. In the result of the research, the data were compiled, as well as the so far unpublished information was obtained on nurse educational work in the fertilization clinics, on the nurse’s personality self-feeling, on the obtaining the additional knowledge for the performance of nursing work duties. The aim of the work has been achieved
Mass Educational Work in the Assisted Reproduction Clinics in Latvia
Keywords: Medicīna: māsu izglītošana; mediciniskā apaugļošana; nurses education; medical conception